Experimental investigation on effect of MgO nanoparticles on cold flow properties, performance, emission and combustion characteristics of waste cooking oil biodiesel - Ranjan, Alok; Dawn, S.S.; Jayaprabakar, J.; Nirmala, N.; Saikiran, K.; Sai Sriram, S. (Fuel (Guildford), 2018)
[Display omitted] •MgO nanoparticles blended test fuels showed improved CFPP & PP.•The addition of MgO nanoparticles did not change other fuel property significantly.•BP, BSFC and BTE of B100W30A, B20W30A and B10W30A were higher than B100, B20 and B10.•MgO blended test fuels emitted less CO, HC, NOx but more CO2.•Combustion of MgO nanoparticles blended biodiesel was better. Commercialization and effective use of biodiesel is still unattained due to its poor cold storage property. Biodiesel produced from waste cooking oil (WCO) using methanol was blended with 0%, 80% and 90% petroleum-based diesel (PBD) fuel and 20 ppm, 30 ppm, 40 ppm and 50 ppm of magnesium oxide (MgO) nanoparticles. The test fuels quality was found to be within limits of the ASTM standards. 30 ppm concentration of MgO nanoparticles showed improvement in cloud point (CP), cold filter plugging point (CFPP) and pour point (PP) of the test fuels. The results showed that the brake specific fuel consumption (BSFC) of B100W30A, B20W30A and B10W30A fuels were 28.2%, 9.48%, and 2.45% higher than the B100, B20 and B10 fuel respectively. PBD showed lower BSFC but higher brake power (BP) and brake thermal efficiency (BTE) when compared to the other test fuels. The BTE and BP of the B100W30A, B20W30A and B10W30A fuels were 4.57% and 1.17% on an average higher than those of B100, B20 and B10 respectively. In general, MgO nanoparticles blended fuel released relatively lesser emissions than B100, B20, B10 and PBD. Combustion analysis of nanoparticles blended fuel was better than other test fuels and comparable with PBD.